Co-Amorphous Solid Dispersions: A Strategy for Improving Poorly Soluble Drug Delivery using Amino Acids and Hydrophilic Carriers - Jitendra Gupta, (Asian Journal of Pharmaceutics (AJP), 2025)
Class II drugs in the Biopharmaceutical Classification System (BCS) are characterized by low solubility and high permeability, necessitating enhanced dissolution to improve their bioavailability and therapeutic efficacy. This review focuses on solid dispersion (SD) strategies, particularly using amino acids (AAs), to enhance the aqueous solubility of compounds, including hydrogen bonding, ionic interactions, and π–π stacking. The review also outlines various techniques for preparing amorphous SDs, such as hot melt extrusion, spray drying, and solvent evaporation, highlighting their scalability and feasibility for pharmaceutical manufacturing. Due to their unique physicochemical properties, AAs serve as effective co-formers in SDs, contributing to the stabilization of the amorphous state and preventing drug recrystallization, a significant limitation in conventional approaches. Finally, the review discusses strategies to overcome key challenges associated with SD and concludes that AA-based systems offer a promising avenue for enhancing the solubility and bioavailability of BCS class II drugs, potentially leading to improved clinical efficacy and patient outcomes.